Psychological peculiarities and family emotional communications of the mothers of drug addicts - Zh. V. Bereza; E. R. Isaeva; S. V. Gorbatov; D. S. Antipina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The paper is devoted to study of peculiarities of emotional communication in families of drug addicts as well as personal characteristics of their mothers, and possible violations in receiving of social assistance. 91 families have been surveyed: 30 families of healthy individuals and 61 families of patients with drug addiction. Survey included: level of co-dependence, the intensity of psychopathological symptoms, level of anxiety and depressive experience of the mothers of drug addicts, their styles of emotional communication and level of social assistance. Study revealed the negative styles of emotional communications in the parent families of drug addicts in comparison with the styles of emotional communications in the families of healthy persons. The mothers of drug addicts differed from the mothers of healthy persons with increased level of paranoid features, suspiciousness, high hostility, anxiety, increased number of phobic fears and obsessions; they are less socially integrated, and are reluctant to seek emotional and instrumental support from others.